2018
DOI: 10.3389/fonc.2018.00476
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungus Isolated From Achyrocline satureioides Exhibits Selective Antiglioma Activity—The Role of Sch-642305

Abstract: Glioblastoma is the most devastating primary brain tumor. Current treatment is palliative, making necessary the development of new therapeutic strategies to offer alternatives to patients. Therefore, endophytes represent an interesting source of natural metabolites with anticancer potential. These microorganisms reside in tissues of living plants and act to improve their growth. Evidence revealed that several medicinal plants are colonized by endophytic fungi producer of antitumor metabolites. Achyrocline satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…ROS consists of highly reactive ions and free radicals, including hydrogen peroxide (H 2 O 2 ), superoxide (O 2 – • ), hydroxyl radical ( • OH), and singlet oxygen ( 1 O 2 ). It was well-known that ROS levels have been demonstrated as a key factor in various cell signal ways. The imbalance of the intracellular ROS level can cause a series of damage to cells, such as the induction of cell cycle arrest in the G2/M or G0/G1 phase. , To investigate whether the cell cycle arrest triggered by TFs was mediated by ROS, the intracellular ROS levels were determined by measuring the fluorescence intensity of DHE as well as DCF. As shown in Figure A, after exposure to TFs for 10 min, the fluorescence intensity of DHE in SW480 cells decreased sharply and fluctuated slowly within 125 min, showing a dose-dependent manner (Figure S3 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…ROS consists of highly reactive ions and free radicals, including hydrogen peroxide (H 2 O 2 ), superoxide (O 2 – • ), hydroxyl radical ( • OH), and singlet oxygen ( 1 O 2 ). It was well-known that ROS levels have been demonstrated as a key factor in various cell signal ways. The imbalance of the intracellular ROS level can cause a series of damage to cells, such as the induction of cell cycle arrest in the G2/M or G0/G1 phase. , To investigate whether the cell cycle arrest triggered by TFs was mediated by ROS, the intracellular ROS levels were determined by measuring the fluorescence intensity of DHE as well as DCF. As shown in Figure A, after exposure to TFs for 10 min, the fluorescence intensity of DHE in SW480 cells decreased sharply and fluctuated slowly within 125 min, showing a dose-dependent manner (Figure S3 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, wound healing assay was performed under low serum (2% fetal bovine serum) condition to validate that the filling of gap is the result of collective migration of MDA-MB-231 and MCF-7 cells, not the proliferation of cells. Accumulating body of evidence suggest that the bioactive compounds of various fungal endophytes possess potential cytotoxic ability, suppression of proliferation, and cell migration of cancer cells including MDA-MB-231 and MCF-7. The current study showed that bioactive compounds produced from the endophyte C. gloeosporioides significantly inhibited the filling of wound created in MDA-MB-231 and MCF-7 cells.…”
Section: Resultsmentioning
confidence: 57%
“…Accumulating body of evidence suggest that the bioactive compounds of various fungal endophytes possess potential cytotoxic ability, suppression of proliferation, and cell migration of cancer cells including MDA-MB-231 and MCF-7. 50 52 The current study showed that bioactive compounds produced from the endophyte C. gloeosporioides significantly inhibited the filling of wound created in MDA-MB-231 and MCF-7 cells. Therefore, the wound healing ability induced by the EA extract of C. gloeosporioides indicates that the bioactive compound produced by the endophyte C. gloeosporioides may appear to be an effective lead molecule in the treatment of breast cancer.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations